The Future of Face Recognition - Bin Ahmad, Muhammad Syafiq Asyraff (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Face recognition has gained popularity in pattern recognition for the future applications in the fields of commercial and law enforcement. It has significant attention due to availability of feasible technologies, including in mobile solutions. Research in automatic face recognition has been conducted since the 1960s, but the problem is still largely unsolved. Last decade has provided significant progress in this area owing to advances in face modelling and analysis techniques. Although systems have been developed for face detection and tracking, reliable face recognition still offers a great challenge to computer vision and pattern recognition researchers. There are several reasons for recent increased interest in face recognition, including rising public concern for security, the need for identity verification in the digital world, face analysis and modelling techniques in multimedia data management and computer entertainment. In this chapter, we have discussed face recognition processing, including major components such as face detection, tracking, alignment and feature extraction, and it points out the technical challenges of building a face recognition system. We focus on the importance of the most successful solutions available so far. The final part of the chapter describes chosen face recognition methods and applications and their potential use in areas not related to face recognition.Â Keywords: Face Recognition, Biometric Identification, Methods, Applications, Image Processing